Dynamic Warm-up and Gentle Stretching Exercises to Success in Jumping Events; An Experimental Approach - Faisal Rasool; Dr. Muhammad Niamat Ullah; Dr. Wasim Khan; Umar Farooq; Muhammad Imran; Muhammad Husnain (Al-Qanṭara, 2023)
Purpose: Warm-ups are an important component of physical activity, particularly for athletes since they help the body to get ready for the physical action of a sport. Dynamic warm-ups and gentle stretching are widely used by athletes to improve performance and prevent injury. The purpose of this study is to find out how a dynamic warm-up and moderate stretching affect jumping ability of novice male athletes. Method: Forty-five (45) beginning male athletes with an average age of 21 years took part in this study. The participants were divided into three groups at random: a control group (n=15), a dynamic warm-up group (n=15), and a gentle stretching group (n=15). Each participant counterbalanced the two exercise regimens for six weeks using a randomized crossover research design. Accordingly, pre- and post-test data were gathered and thereafter analyzed using the mean, standard deviation, and t-test in SPSS version 25. Results: The findings demonstrated that the Control Group had substantially lower mean scores than the Dynamic Warm-up Training and Gentle Stretching Training groups, with a significance level of.000. With a 95% confidence range spanning from -17.758 to -10.197, the mean difference between the Control Group and Dynamic Warm up training group was -13.977. With a 95% confidence range spanning from -14.018 to -6.517, the mean difference between the Control Group and the Gentle Stretching Training group was -10.268, according to the study. Conclusion: The results of this research showed that dynamic warm-up and gentle stretching interventions considerably enhanced the jumping abilities of beginner male athletes. The dynamic warm-up intervention was more effective in improving jump performance when gentle stretching was added. Implications: According to this study, a dynamic warm-up and gentle stretching exercises may help beginner male athletes to jump higher. The dynamic warm-up intervention, however, was more successful in improving jump performance. Keywords: Effects, dynamic warm-up, gentle stretching, beginner athletes & jump performance